Mapping spatial-temporal skipjack tuna habitat as a reference for Fish Aggregating Devices (FADs) settings in Makassar Strait, Indonesia - RACHMAT HIDAYAT; MUKTI ZAINUDDIN; ACHMAR MALLAWA; MUZZNEENA AHMAD MUSTAPHA; A. RANI SAHNI PUTRI (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Hidayat R, Zainuddin M, Mallawa A, Mustapha MA, Putri ARS. 2021. Mapping spatial-temporal skipjack tuna habitat as a reference for Fish Aggregating Devices (FADs) settings in Makassar Strait, Indonesia. Biodiversitas 22: 3637-3647. Skipjack tuna (Katsuwonus pelamis) has a high economic value in the international market. Catching skipjack tuna using fish aggregating devices (FADs) without knowing its habitat characteristics can damage the ecosystem. This study aimed to determine suitable fishing areas for setting skipjack’s FADs. The data used included that on catch, sea surface temperature (SST), and sea surface chlorophyll-a (SSC) in the Makassar Strait obtained for 2017-2019. The generalized additive model (GAM) and empirical cumulative distribution function (ECDF) analyses were used to investigate the skipjack’s tuna habitat. A pelagic habitat index (PHI), with PHI > 75%, was applied to determine suitable FAD positions. The gravity center of the skipjack tuna habitat for ten months (January-October 2020) was calculated to validate the model’s results. The results showed that the optimum SST range was from 28.78°C to 31.25°C, while the SSC from 0.18 to 0.28 mg m-3. The best skipjack habitats in the southern Makassar Strait are criterion 4 (PHI > 90%) and criterion 3 (PHI = 85-90%), having a relatively high consistency of the average PHI values. These results can help determine the optimal positions for setting FADs to benefit the global management and sustainable development of skipjack tuna fisheries.